Analisis Naskah Monolog “Apakah Kita Sudah Merdeka” Karya Putu Wijaya - Ailsa Ardelia; Zaky Mubarok (Lembaga Pengembangan Kinerja Dosen, 2023)
This research analyzes two monologue scripts by renowned writer Putu Wijaya, titled